Pengaruh Kompetensi Terhadap Kinerja Aparatur Sipil Negara di Dinas Perikanan Kabupaten Pesisir Barat - Iqbal Hidayat, Muhammad; Corry Wardhani, Andy; Noviyanti, Rinda (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
The performance of the Civil Servant is the result of work achieved by an ASN, with varying levels of ability and skills in carrying out and completing their work. Performance measurement is an organizational process of determining the parameters for achieving work programs and activities that have been carried out. Generally, this applies for one budget year. The purpose of this study is to determine and analyze how much influence competence has on ASN performance in the West Coast Fisheries Service. From this study, it can be produced to determine the level of organizational progress in achieving targets and evaluations as well as input materials for preparing future programs so that performance measurement will be greatly influenced by individual competence and compensation provided by the organization. The influence of the independent variable, competence (X1) on the dependent variable, performance (Y), through the analysis of the coefficient of determination output, obtained an Adjusted R Square value of 0.435.